Wars of Choice or Crime? The National Interest, State Crime and Official Overseas British Military Interventions Since 1945. (1st April 2014) - Alan Doig
Abstract : Since 1945 British governments, as a matter of official policy, have undertaken a number of military interventions against another sovereign state. Some interventions were justified on the grounds that they delivered United Nations Security Council Resolutions (UNSCR) whether through another international organization such as the North atlantic Treaty Organisation (NaTO) or as a joint state activity. Others have been justified on humanitarian grounds or in terms of a regional or global responsibility to maintain peace and security. International law and international standards provide a framework for the legitimacy or otherwise of any intervention by one sovereign state in the affairs of another sovereign state; to act in breach of them would be a state crime. as a liberal democratic country the United Kingdom (UK) would not be expected so to act. On the other hand, successive UK governments have emphasized the role of the national interest as a major official criterion for intervention, in part where authorization has been, or claimed to have been, provided by a UNSCR or, increasingly, where the UK intervenes without such an authorization. This article asks if the formal reasons for any of the interventions give grounds for questioning their legality under international law and why a liberal democratic state may pursue an approach amounting to state crime. It concludes by suggesting that a liberal democratic state such as the UK has both the capacity and motivation for state crime at international level and, while the opportunities for so acting may be limited, the pursuit of the national interest is an ever-present potential for initiating or engaging in interventions whose justification under international law or other international standards may be tenuous at best or illegal at worst.